Process modelling of biomass conversion to biofuels with combined heat and power - Sharma, A.; Shinde, Yogesh; Pareek, V.; Zhang, D. (2015)
© 2015 Elsevier Ltd. A process model has been developed to study the pyrolysis of biomass to produce biofuel with heat and power generation. The gaseous and solid products were used to generate heat and electrical power, whereas the bio-oil was stored and supplied for other applications. The overall efficiency of the base case model was estimated for conversion of biomass into useable forms of bio-energy. It was found that the proposed design is not only significantly efficient but also potentially suitable for distributed operation of pyrolysis plants having centralised post processing facilities for production of other biofuels and chemicals. It was further determined that the bio-oil quality improved using a multi-stage condensation system. However, the recycling of flue gases coming from combustor instead of non-condensable gases in the pyrolyzer led to increase in the overall efficiency of the process with degradation of bio-oil quality.